Докажите, что значение выражения не зависит от переменной x:1) (x-0,7)×(0,7+x)+5-x^2=2) (5-0,9x)×(0,9x+5)-10+0,81x^23) (x-0,2)×(0,2+x)+(4-x)×(4+x)4) (0,6-x)×(x+0,6)-(2-x)×(x+2)помогиииите...

Докажите, что значение выражения не зависит от переменной x: 1) (x-0,7)×(0,7+x)+5-x^2= 2) (5-0,9x)×(0,9x+5)-10+0,81x^2 3) (x-0,2)×(0,2+x)+(4-x)×(4+x) 4) (0,6-x)×(x+0,6)-(2-x)×(x+2) помогиииите...
Гость
Ответ(ы) на вопрос:
Гость
1) (x-0,7)×(0,7+x)+5-x^2= 0,7x+x^2-0,49-0,7x+5-x^2= -0,49 -доказано 2) (5-0,9x)×(0,9x+5)-10+ 0,81x^2= 4,5x+25-0,81x^2-4,5x-10+ 0,81x^2=15 -доказано 3) (x-0,2)×(0,2+x)+ (4-x)×(4+x)= 0.2x+x^2-0.04-0.2x+16+4x-4x-x^2=15.96-доказано 4) (0,6-x)×(x+0,6)-(2-x)×(x+2)= 0.6x+0.36-x^2-0.6x-2x-4+x^2+2x= -3.64-доказано
Не нашли ответ?
Ответить на вопрос
Похожие вопросы